2020
DOI: 10.1016/j.ijfoodmicro.2019.108392
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of selected viral and bacterial pathogens and microbiological quality of fresh and frozen strawberries sold in Spain

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 3.0 de Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…in berries. Even though no bacterial pathogenic microorganisms have usually been found on field and sold retail strawberries (Delbeke et al, 2015;Ortiz-Solà et al, 2019a), Salmonella spp. and Listeria monocytogenes were able to survive on the fruit surface at different stored temperatures (Ortiz-Solà et al, 2019b;Sreedharan et al, 2015), and L. monocytogenes could grow in the conditions in which strawberries are stored (Siro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…in berries. Even though no bacterial pathogenic microorganisms have usually been found on field and sold retail strawberries (Delbeke et al, 2015;Ortiz-Solà et al, 2019a), Salmonella spp. and Listeria monocytogenes were able to survive on the fruit surface at different stored temperatures (Ortiz-Solà et al, 2019b;Sreedharan et al, 2015), and L. monocytogenes could grow in the conditions in which strawberries are stored (Siro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry (Fragaria × ananassa) production and consumption has practically doubled over the past 15 years (Indexbox, 2017), being. Strawberries are generally considered a safe product, and some authors reported the absence of pathogenic microorganisms in the sampled fruits (Ortiz-Solà, 2020). However, mold growth and loss of firmness of strawberries may cause losses of 10 % to 35 % at retail and at consumer level, respectively, making the control of alterative microbiota a challenge for fruit industry (Kelly, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The safekeeping of consumers over the transmission of zoonotic foodborne infectious disease from diseased animal consumption, unhygienic slaughter houses and unscientific processing means has been a deep concern for centuries. The occurrence of foodborne illness outbreaks requires the intervention of advanced novel processing and preservation techniques to mitigate pathogens and fulfill HACCP requirements (Mendonca et al., 2020; Ortiz‐Solá et al., 2020). Different techniques for the treatment of pathogens in various food products are reported in Table 3.…”
Section: Effective Mitigation Strategies For Food Borne Pathogensmentioning
confidence: 99%